The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH